Assessment of environmental impacts of heavy metal pollution in rice in Nanning, China - Jing Zhang; Peng Li; Siyan Li; Zhongqi Lyu (Scientific Reports)
Abstract Nowadays rice has become one of the world’s staple foods. Rice in southern China is also a staple food for everyone, however, with the development of China’s industrialization model, many industrial areas may be contaminated by heavy metals, leading to contamination of the agricultural areas. With the development of recent years, Nanning has become a heavily industrial development area, and rice is also a favourite staple food. Therefore, it is a matter of concern to detect whether heavy metals contaminate rice in Nanning due to environmental factors. Five administrative villages were selected from 12 districts, and 20% of the natural villages were randomly selected for soil and water sample taking using probability distribution points and making the number of samples in each village evenly distributed. The single gene index pollution method and Nemerow composite pollution index method was used to evaluate whether heavy metals polluted the crops. Rice was evaluated through the national standard of Food Safety and Food Contaminant Limits. The survey shows that the heavy metal pollution of rice is moderate, especially cadmium pollution is more serious, but the risk of environmental factors in the Nanning area has a small impact on the overall safety and quality of rice, which is still within the controllable range. The total exceedance rate of heavy metals in the surveyed local rice was 20.95%, and the exceedance rate of paddy rice was 33.33%. The exceedance rates of lead, cadmium, inorganic arsenic, and total mercury in rice were 2.23%, 17.88%, 0.56%, and 0.84% respectively. Cadmium was identified as the primary heavy metal contaminant in local rice, with the highest detected concentration reaching 1.23 mg/kg, which is 6.15 times above the limit set by national health standards. This study shows that the concentration of heavy metals in the environment of Nanning Province is low, and the risk caused by environmental factors has relatively little impact on the safety and quality of rice. However, since the pollution of heavy metals will continue to enrich the food chain with time, long-term use will also cause harm to the human body. Therefore, it is necessary to raise the attention of local governments in rice-producing areas to food safety, and then take effective measures to improve local heavy metal detection technology, improve crop quality, and protect people’s food safety.